Ultrathin α-MnO2 Nanosheets Wrapped on Acanthosphere-like Microspheres with Highly Reversible Performance for Energy Storage. (1st September 2017) - Peng, Huarong; Li, Yanhong; Liu, Chunli; Wei, Xijun; Dong, Hongmei; Yang, Lin; Zhang, Yunhuai; Xiao, Peng
Abstract: Architecturally assembling primary building blocks into the expected geometric heterostructure is a tremendous challenge due to the interfaces dislocation and stretch resulting from the lattice-mismatch between heterogeneous building blocks. Although different dimensional nanomaterials have been synthesized, the branched acanthosphere-like hierarchical architecture is needed to be developed and the growth mechanism should be investigated. Here we design and fabricate an acanthosphere-like NiCo2 O4 @α-MnO2 heterostructures architecture by an "in situ growth" technique of two-steps hydrothermal method. The as-prepared acanthosphere-like NiCo2 O4 @α-MnO2 microspheres (denoted as AM-NCM) have a diameter of 5 ∼ 7 um with a highly open and interstitial three dimensional (3D) architecture formed by α-MnO2 ultrathin nanosheets leading to faster ion diffusion and improved charge transfer kinetics. Therefore, the hybrid electrodes exhibits exceptional specific capacitances of 695 F g −1 (2.17 F cm −2 ) at the current densities of 3.2 A g −1 (10 mA cm −2 ) and good cycling electrochemical stability with only 2.4% capacitance loss after 1000 cycles and still maintains 92% of its initial value after 6000 cycles. The outstanding performance of the branched AM-NCM reveals its potential to be a promising material for energy storage, and also inspires continued research on the formation of branched hierarchical architecture as energy storage materials.